Feeling stretched or compressed? The multiple mechanosensitive responses of wood formation to bending. (24th January 2018) - Roignant, Jeanne; Badel, Éric; Leblanc-Fournier, Nathalie; Brunel-Michac, Nicole; Ruelle, Julien; Moulia, Bruno; Decourteix, Mélanie
Abstract: Background and Aims: Trees constantly experience wind, perceive resulting mechanical cues, and modify their growth and development accordingly. Previous studies have demonstrated that multiple bending treatments trigger ovalization of the stem and the formation of flexure wood in gymnosperms, but ovalization and flexure wood have rarely been studied in angiosperms, and none of the experiments conducted so far has used multidirectional bending treatments at controlled intensities. Assuming that bending involves tensile and compressive strain, we hypothesized that different local strains may generate specific growth and wood differentiation responses. Methods: Basal parts of young poplar stems were subjected to multiple transient controlled unidirectional bending treatments during 8 weeks, which enabled a distinction to be made between the wood formed under tensile or compressive flexural strains. This set-up enabled a local analysis of poplar stem responses to multiple stem bending treatments at growth, anatomical, biochemical and molecular levels. Key Results: In response to multiple unidirectional bending treatments, poplar stems developed significant cross-sectional ovalization. At the tissue level, some aspects of wood differentiation were similarly modulated in the compressed and stretched zones (vessel frequency and diameter of fibres without a G-layer), whereas other anatomical traits (vessel diameter, G-layer formation, diameter of fibres with a G-layer and microfibril angle) and the expression of fasciclin-encoding genes were differentially modulated in the two zones. Conclusions: This work leads us to propose new terminologies to distinguish the 'flexure wood' produced in response to multiple bidirectional bending treatments from wood produced under transient tensile strain (tensile flexure wood; TFW) or under transient compressive strain (compressive flexure wood; CFW). By highlighting similarities and differences between tension wood and TFW and by demonstrating that plants could have the ability to discriminate positive strains from negative strains, this work provides new insight into the mechanisms of mechanosensitivity in plants.